Stories from Around the World - Heather Amery (England UsBorne Publishing, 2009)
Traditional stories from all around the world gathered here in this magical collection. Tales of brave heroes and heroines are retold alongside tales of wonderful magic, of strange and faithful creatures, and of how things first began. These fascinating stories are narrated in such a way that young listeners and young readers will find them easy to understand and enjoy.
Keywords: TL - Folktales -- TL - Folktales